The Effects of Lactic Acid Bacteria and Enzyme Mixture Inoculants on Silage Fermentation Characteristics and Feed Values of Silage Prepared from Alfalfa Harvested at Different Maturities - Berrin Okuyucu; Selma Büyükkılıç Beyzi; Mehmet Levent Özdüven (Turkish Journal of Agriculture: Food Science and Technology)
This study was carried out to determine the effects of lactic acid bacteria+ enzyme (LAB+E) inoculants on the fermentation characteristics and feed values of silages prepared from alfalfa harvested at three maturity stages. Alfalfa was harvested at the early, middle and late flowering stages. Sil-All (Alltech, UK) were used as LAB+E inoculants. Inoculants were applied to the silages at the rates of 1×105, 5×105 and 1×106 cfu/g levels in 1 liter capacity plastic bags. The bags were stored at 20±2°C under the laboratory conditions. Three bags from each group were sampled for chemical and microbiological analyses on the 45th day after ensiling. The results showed that LAB+E inoculants reduced pH values and ammonia-nitrogen content, whereas increased lactic acid contents and lactobacillus count of alfalfa silages. High doses LAB+E inoculant decreased neutral detergent fiber and acid detergent fiber content, increased in vitro organic matter digestibility and metabolic energy of alfalfa silages. It has been demonstrated that the most effective application dose of LAB+E inoculant to improve fermentation and feed value of alfalfa silage was 1×106 cfu/g, but 1x105 and 5×105 cfu/g level can also be considered as effective dose.